2016
DOI: 10.1038/srep33026
|View full text |Cite
|
Sign up to set email alerts
|

Polysialic acid sustains cancer cell survival and migratory capacity in a hypoxic environment

Abstract: Polysialic acid (polySia) is a unique carbohydrate polymer expressed on the surface of NCAM (neuronal cell adhesion molecule) in a number of cancers where it modulates cell-cell and cell-matrix adhesion, migration, invasion and metastasis and is strongly associated with poor clinical prognosis. We have carried out the first investigation into the effect of polySia expression on the behaviour of cancer cells in hypoxia, a key source of chemoresistance in tumours. The role of polysialylation and associated tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 57 publications
0
38
0
Order By: Relevance
“…NCAM assemble with NCAMs of adjacent cells via homophilic interactions or associates with other protein via heterophilic interactions (Cavallaro et al, 2001;Berezin, 2010;Cavallaro and Dejana, 2011). The disruption of NCAM function affects signaling pathways and has detrimental consequences for cell viability (Shichi et al, 2011;Elkashef et al, 2016). The disruption of NCAM function affects signaling pathways and has detrimental consequences for cell viability (Shichi et al, 2011;Elkashef et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…NCAM assemble with NCAMs of adjacent cells via homophilic interactions or associates with other protein via heterophilic interactions (Cavallaro et al, 2001;Berezin, 2010;Cavallaro and Dejana, 2011). The disruption of NCAM function affects signaling pathways and has detrimental consequences for cell viability (Shichi et al, 2011;Elkashef et al, 2016). The disruption of NCAM function affects signaling pathways and has detrimental consequences for cell viability (Shichi et al, 2011;Elkashef et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that FGFR is one of NCAM binding partners in modulation of signal transduction (Francavilla et al, 2007). The disruption of NCAM function affects signaling pathways and has detrimental consequences for cell viability (Shichi et al, 2011;Elkashef et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since cell surface sialylation and polysialylation are prognostic markers of several tumors [21], we then quantified membrane bound sialic acids and polysialic acids of Kelly cells cultured in the absence or presence of 100 µM MGO. We found that MGO treatment increased the total sialic acids on cell surface proteins by nearly 50% ( Figure 3A).…”
Section: Glycation Leads To Increased Sialylation and Increased Exprementioning
confidence: 99%